PENERAPAN TEKNOLOGI BUDIDAYA TANAMAN CAMPURAN RUMPUT DAN LEGUM UNGGUL SEBAGAI SUMBER PAKAN SAPI BALI DI DESA KENDERAN KABUPATEN GIANYAR - Trisnadewi, A. A. A. S.; Suarna, I W.; Yadnya, T. G. B.; Cakra, I G. L. O.; Budiasa, I K. M. (Buletin Udayana Mengabdi, 2018)
The community services conducted in the cage group of Simantri 256 Gapoktan Sedana Merta and was attended by 23 of members, farmers and companion officer of Simantri. The community services preceded by explanation and discussion regarding mixed cultivation technology of introduce grass and leguminose and also supported with brochure's. At the end of the activities, members of Simantri 256 made a demoplot of mixed cultivation technology of introduce grass and leguminose, then could use as an example in developing of fodder forage for the group members of Simantri 256 and other farmers in Kenderan Village. Members of Simantri 256 are very excited by the information that provided by the team of comunity services. During the The community services conducted in the cage group of Simantri 256 Gapoktan Sedana Merta and was attended by 23 of members, farmers and companion officer of Simantri. The community services preceded by explanation and discussion regarding mixed cultivation technology of introduce grass and leguminose and also supported with brochure's. At the end of the activities, members of Simantri 256 made a demoplot of mixed cultivation technology of introduce grass and leguminose, then could use as an example in developing of fodder forage for the group members of Simantri 256 and other farmers in Kenderan Village. Members of Simantri 256 are very excited by the information that provided by the team of comunity services. During the activities is filled with discussions about the problems faced by farmers, especially bali cattle nursering. Many questions asked by farmers such as the function of forage legumes, the offering technique of Gliricidia, and the causes of cows failed pregnancy. The question is answered by the team of community services, so it’s easy for farmers to understand the explanation. Models developed in making demoplot of mixed cultivation technology of introduce grass and leguminose is grass - grass - leguminose pattern (Brachiaria decumbens – Panicum maxsimum – Centrocema pubescens or Brachiaria decumbens – Panicum maxsimum – Clitoria ternatea). It could be concluded that members of Simantri 256 Gapoktan Merta Sedana very enthusiastic in this community service through explanation and discussion about the mixed cultivation technology of introduce grass and leguminose, which was attended by 24 members of Simantri farmers and other farmers with high extended catagory, it’s formed a demoplot of mixed cultivation technology of introduce grass and leguminose, and could be an example in developing of forage.